Campaign for Clean and Healthy Living Behaviors on Anxiety Levels and Compliance with Clean and Healthy Living During the Covid-19 Pandemic - Suraya Mansur; Nurhayani Saragih; Isiaka Zubair Aliagan (Ikatan Sarjana Komunikasi Indonesia, 2021)
This research concerns the health communication campaign for Clean and Healthy Lifestyle (PHBS) during the Covid-19 pandemic among students of the graduate school of the University of Mercu Buana. This research found that the social learning theory proves effective in the campaign which leads to a change in society’s behaviour. The theory used in this research is Albert Bandura's social learning theory. This research used positivistic paradigm. The method used in this research is a survey explanatory method and quantitative approach. The population is students of the graduate school at the University of Mercu Buana Jakarta. The sampling is conducted using purposive sampling techniques to 100 respondents, with a sampling error of 5%. The technique of data analysis used in this research is simple regression analysis. The result shows that PHBS Campaign has no significant effect on Anxiety Level. PHBS Campaign has a significant effect on Compliance Level. Anxiety Level has no significant effect on Compliance Level. PHBS Campaign has no significant effect on Compliance Level through Anxiety Level.